Clinical outcomes in patients with chronic hepatitis C after direct-acting antiviral treatment: a prospective cohort study. Issue 10179 (6th April 2019) - Carrat, Fabrice; Fontaine, Hélène; Dorival, Céline; Simony, Mélanie; Diallo, Alpha; Hezode, Christophe; De Ledinghen, Victor; Larrey, Dominique; Haour, Georges; Bronowicki, Jean-Pierre; Zoulim, Fabien; Asselah, Tarik; et al.
Summary: Background: Although direct-acting antivirals have been used extensively to treat patients with chronic hepatitis C virus (HCV) infection, their clinical effectiveness has not been well reported. We compared the incidence of death, hepatocellular carcinoma, and decompensated cirrhosis between patients treated with direct-acting antivirals and those untreated, in the French ANRS CO22 Hepather cohort. Methods: We did a prospective study in adult patients with chronic HCV infection enrolled from 32 expert hepatology centres in France. We excluded patients with chronic hepatitis B, those with a history of decompensated cirrhosis, hepatocellular carcinoma, or liver transplantation, and patients who were treated with interferon-ribavirin with or without first-generation protease inhibitors. Co-primary study outcomes were incidence of all-cause mortality, hepatocellular carcinoma, and decompensated cirrhosis. The association between direct-acting antivirals and these outcomes was quantified using time-dependent Cox proportional hazards models. This study is registered withClinicalTrials.gov, numberNCT01953458 . Findings: Between Aug 6, 2012, and Dec 31, 2015, 10 166 patients were eligible for the study. 9895 (97%) patients had available follow-up information and were included in analyses. Median follow-up was 33·4 months (IQR 24·0–40·7). Treatment with direct-acting antivirals was initiated during follow-up in 7344 patients, and 2551 patients remained untreated at the final follow-up visit. During follow-up, 218 patients died (129 treated, 89 untreated), 258 reported hepatocellular carcinoma (187 treated, 71 untreated), and 106 had decompensated cirrhosis (74 treated, 32 untreated). Exposure to direct-acting antivirals was associated with increased risk for hepatocellular carcinoma (unadjusted hazard ratio [HR] 2·77, 95% CI 2·07–3·71) and decompensated cirrhosis (3·83, 2·29–6·42). After adjustment for variables (age, sex, body-mass index, geographical origin, infection route, fibrosis score, HCV treatment-naive, HCV genotype, alcohol consumption, diabetes, arterial hypertension, biological variables, and model for end-stage liver disease score in patients with cirrhosis), exposure to direct-acting antivirals was associated with a decrease in all-cause mortality (adjusted HR 0·48, 95% CI 0·33–0·70) and hepatocellular carcinoma (0·66, 0·46–0·93), and was not associated with decompensated cirrhosis (1·14, 0·57–2·27). Interpretation: Treatment with direct-acting antivirals is associated with reduced risk for mortality and hepatocellular carcinoma and should be considered in all patients with chronic HCV infection. Funding: INSERM-ANRS (France Recherche Nord & Sud Sida-HIV Hépatites), ANR (Agence Nationale de la Recherche), DGS (Direction Générale de la Santé), MSD, Janssen, Gilead, AbbVie, Bristol-Myers Squibb, and Roche.